2019
DOI: 10.3389/fimmu.2019.02321
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Macrophage tnfa Expression via Cyclooxygenase and Prostaglandin E2 in vivo

Abstract: Macrophage phenotypes are poorly characterized in disease systems in vivo. Appropriate macrophage activation requires complex coordination of local microenvironmental cues and cytokine signaling. If the molecular mechanisms underpinning macrophage activation were better understood, macrophages could be pharmacologically tuned during disease situations. Here, using zebrafish tnfa:GFP transgenic lines as in vivo readouts, we show that physiological hypoxia and stabilization of Hif-1α promotes macrophage tnfa exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 68 publications
2
32
0
Order By: Relevance
“…Previously, others and us showed that following caudal fin fold amputation, zebrafish macrophages are recruited and acquire different functional phenotypes, very similar to that of mammals (8,9,(30)(31)(32). After injury, macrophages adopt a pro-inflammatory (M1-like) phenotype expressing proinflammatory cytokines such as tnfa, tnfb, il1b and il6 (8,(32)(33)(34)(35). While repair proceeds, macrophages switch toward noninflammatory phenotypes expressing cxcr4, ccr2 and tgfb1 (34).…”
Section: Introductionmentioning
confidence: 91%
“…Previously, others and us showed that following caudal fin fold amputation, zebrafish macrophages are recruited and acquire different functional phenotypes, very similar to that of mammals (8,9,(30)(31)(32). After injury, macrophages adopt a pro-inflammatory (M1-like) phenotype expressing proinflammatory cytokines such as tnfa, tnfb, il1b and il6 (8,(32)(33)(34)(35). While repair proceeds, macrophages switch toward noninflammatory phenotypes expressing cxcr4, ccr2 and tgfb1 (34).…”
Section: Introductionmentioning
confidence: 91%
“…There is a compelling list of publications describing the release of pro-inflammatory cytokines from cancer and hypoxic tissues ( Dinarello, 2006 ; Peyssonnaux et al, 2007 ; Popa et al, 2007 ; Heikkilä et al, 2008 ; Xing and Lu, 2016 ; Lewis and Elks, 2019 ; Kammerer et al, 2020 ). Recently, a transcriptomic meta-analysis of human cancers varying in degree of their pro-cachectic potential has been performed to identify new cachectic factors ( Freire et al, 2020 ).…”
Section: The Function Of Immune Cell-derived Sifs May Be Conserved Bementioning
confidence: 99%
“…HIF‐1α knockouts have decreases in IFNγ [77], IL‐1β [51] and IL‐6 [51] leading to excess tissue damage and lower survival [46]. Early HIF‐1α stabilisation increases inflammatory factors leading to myeloid control of infection [48–50], while excessive HIF‐1α can lead to prolonged inflammation and larger TB lesions in later stage disease [51]. In the context of the fungal infection Candida albicans (yellow column), HIF‐1α knockout decreases pro‐inflammatory factors while increasing anti‐inflammatory IL‐10 leading to increased fungal survival [55].…”
Section: Upregulating Hif In Infectionsmentioning
confidence: 99%
“…During early infection, HIF‐1α stabilisation is beneficial for innate immune control of TB. In a zebrafish TB model, using the fish‐adapted pathogen and close genetic relative of Mtb, Mycobacterium marinum (Mm), Hif‐1α stabilisation increased myeloid production of Il‐1β, vital for decreasing bacterial burden via neutrophil nitric oxide (NO) production [48,49], alongside increasing pro‐inflammatory macrophage Tnfa production [50]. The HIF‐induced, host NO response has also shown to be important in a mouse model of TB infection, with HIF‐1α and iNOS in a positive feedback loop, balancing the inflammatory phenotype [51].…”
Section: Upregulating Hif In Infectionsmentioning
confidence: 99%